Hospital financial performance and quality of care – a scoping review of empirical studies. (20th October 2021) - Dubas-Jakóbczyk, K; Kocot, E; Tambor, M; Kostrzewska, O; Szetela, P; Quentin, W
Abstract: Background: Hospitals operate under constant pressure to contain costs and improve the quality of care (Q). The potential association between hospital financial performance (FP) and Q can have two directions: (1) providers with better FP might have a greater capacity to maintain and/or improve Q; (2) a better Q might lead to better FP, i.e. increased revenues, and/or lower costs. The general objective of this study was to identify and map the available evidence on the association between hospital FP and Q. Methods: A scoping review based on the methodological framework outlined by Arksey and O'Malley was conducted. Five databases were used: (1) Medline via PubMed; (2) Embase; (3) Web of Science; (4) Scopus; and (5) EconLit. Search strategy combined multiple terms from three topics: (1) hospital, (2) FP and (3) Q. There was no limit for publication years, but only studies in English were included. Results: After screening 8, 015 records and 129 full text papers, 54 empirical studies were included. They are mostly observational studies, applying diverse regression models, published between 1992 and 2019. FP is most often measured by profitability indicators while Q measures are much more diverse. In the majority of studies, FP measures are used as dependent variables, thus the impact of Q on FP is assessed. The comparability of the studies' results is limited, yet a general overview shows that in the majority of papers, a positive association between hospital FP and Q is identified (positive in 24 studies and positive or mixed in 10). The studies' authors emphasize numerous limitations related to both, the data used and the methods applied including the ability to identify associations yet not causality. Conclusions: There seems to be a growing interest in exploring the association between FP and Q. Our review provides a broad overview of the existing literature and helps to identify areas for further investigations. Key messages: There is a great diversity of empirical studies on the association between hospital FP and Q, but the majority focuses solely on the United States market. An overview of the existing studies suggests that, although numerous additional factors need to be considered, hospitals might be able to simultaneously improve Q and profitability.